1993
DOI: 10.1002/j.1552-4604.1993.tb03901.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Partial Escape of Renin‐Angiotensin‐Aldosterone Blockade in Patients with Acute Myocardial Infarction Treated with Ace Inhibitors

Abstract: Angiotensin-converting enzyme (ACE) inhibitors have been designed to block the renin-angiotensin system and can represent an effective therapeutic approach in those settings where such a system is active, such as myocardial infarction. In a randomized placebo-controlled study, 10 patients with acute myocardial infarction allocated to treatment with increasing doses of zofenopril calcium and 10 patients allocated to placebo were studied in hospital, within 24 hours from symptoms, during 11 sampling periods to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 19 publications
1
52
0
3
Order By: Relevance
“…[3][4][5][6][7][8] Although previous studies have reported high plasma aldosterone levels in myocardial infarction, these observations have most often been limited by their small sample size, heterogeneous study populations, late measurements of aldosterone (often days to months after the onset of myocardial infarction), and inconclusive results with regard to the association of aldosterone with further clinical events. 9 -12 The aim of the present study was to assess early plasma aldosterone release in patients presenting with ST-elevation myocardial infarction (STEMI) within 24 hours of symptom onset and to determine whether aldosterone levels are related to adverse outcomes in this setting.…”
Section: Editorial P 2572 Clinical Perspective P 2610mentioning
confidence: 99%
“…[3][4][5][6][7][8] Although previous studies have reported high plasma aldosterone levels in myocardial infarction, these observations have most often been limited by their small sample size, heterogeneous study populations, late measurements of aldosterone (often days to months after the onset of myocardial infarction), and inconclusive results with regard to the association of aldosterone with further clinical events. 9 -12 The aim of the present study was to assess early plasma aldosterone release in patients presenting with ST-elevation myocardial infarction (STEMI) within 24 hours of symptom onset and to determine whether aldosterone levels are related to adverse outcomes in this setting.…”
Section: Editorial P 2572 Clinical Perspective P 2610mentioning
confidence: 99%
“…The increase in renin activity stimulates the conversion of Ang I and ultimately Ang II, which largely limits the efficacy of RAS inhibition (27,28). The increased renin can also act through the prorenin/ renin receptor (10), which may cause renal and cardiovascular damages independent of Ang II (29).…”
mentioning
confidence: 99%
“…This unfortunately is not the case. Several investigators have demonstrated that the use of ACEinhibitors initially causes an acute decrease in the concentration of aldosterone, but with continued use, this suppression is not sustained (59)(60)(61)(62).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%